Impact of Legal Traditions on Forensic Mental Health Treatment Worldwide - Beis, Pavlos; Graf, Marc; Hachtel, Henning (Frontiers in Psychiatry, 2022)
Background: Forensic psychiatry is a subspecialty dealing with the diagnosis and treatment of mentally ill offenders. However, forensic treatment standards vary. Differences arise among forensic treatment standards, due to variations in either the legal framework, the general psychiatric treatment standards, or the forensic training standards. Thus, to date there is no evidence-based pattern for how forensic services should be organized and provided. Aims: The aim of this article is to compare forensic services in various countries in order to contribute to the current debate on international forensic treatment standards, by informing about existing differences in available policies. Methods: This scoping review was conducted by reviewing the academic literature regarding forensic treatment around the world. Studies were identified from Pub-Med and Google-Scholar. Keywords for the search included “forensic psychiatry”, “mentally ill offenders”, “legal framework”, “jurisdiction”, and the names of geographical regions. Results: Forensic treatment admission varies significantly around the world. There are countries that do not recognize forensic psychiatry as a subspecialty, whereas other countries apply insufficient forensic training. Most countries provide inpatient treatment for mentally ill offenders. However, service organization varies, including where the services are delivered (prisons, high-security hospitals, general psychiatric departments). Forensic services are mainly centralized, although the need for outpatient care is emerging. Discussion: Differences may originate mainly from variations in the legal tradition. These differences combined with the limited evidence on the effectiveness of the intervention imply the need for the optimization of forensic treatment standards on an international level. Therefore, further follow-up studies are needed.